Anisotropic Elastography for Local Passive Properties and Active Contractility of Myocardium from Dynamic Heart Imaging Sequence - Yi Liu; Ge Wang; L. Z. Sun (International Journal of Biomedical Imaging)
Major heart diseases such as ischemia and hypertrophic myocardiopathy are accompanied with significant changes in the passive mechanical properties and active contractility of myocardium. Identification of these changes helps diagnose heart diseases, monitor therapy, and design surgery. A dynamic cardiac elastography (DCE) framework is developed to assess the anisotropic viscoelastic passive properties and active contractility of myocardial tissues, based on the chamber pressure and dynamic displacement measured with cardiac imaging techniques. A dynamic adjoint method is derived to enhance the numerical efficiency and stability of DCE. Model-based simulations are conducted using a numerical left ventricle (LV) phantom with an ischemic region. The passive material parameters of normal and ischemic tissues are identified during LV rapid/reduced filling and artery contraction, and those of active contractility are quantified during isovolumetric contraction and rapid/reduced ejection. It is found that quasistatic simplification in the previous cardiac elastography studies may yield inaccurate material parameters.